Three-dimensional study of the orbit-related structures according to sex, age and skeletal deformities (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the relations between orbit-related structures and sex, age and skeletal deformities using cone-beam computed tomography (CBCT). Methods: This retrospective study evaluated 216 consecutive CBCT scans of patients, who were divided according to: sex (male, n=105; female, n=111), age (A1: 18-32 years, n=71; A2: 33-47 years, n=78; A3: 48-62 years, n=67), and skeletal deformities (Class I, n=70; Class II, n=75; Class III, n=71). The supraorbital foramen (SOF) location, volume of orbit, optic canal (OC) and infraorbital canal (IOC) were evaluated. Results were analyzed using the Gamma model test. The Tukey-Kramer post-hoc test was used to compare the variables with three factors (p